TUNGSTEN-CONTAINING BADDELEYITE. A NEW VARIETY OF ZIRCONIUM OXIDE - Nekrasov I.Ya.; Ananyev V.V. (My University, 1990)
The presence of two unusual zirconium minerals (tungsten-containing baddeleyite and the hydrated zirconium silicate) in the stratiform Algama ore occurrence suggests a new genetic type of tungsten-zirconium mineralization. The tungsten-containing baddeleyite and the newly found zirconium silicate from the Algama ore occurrence were formed under different conditions from the known commercial deposits of baddeleyite in the weathered crust of carbonatite bodies (Palabora, South Africa; Madeira, Brazil), or accessory baddeleyite mineralization in kimberlite, basic rocks of stratified intrusive bodies and nepheline syenites. They were deposited from strongly basic (pH ≈ 10) low-temperature (80 to 180° C) colloidal suspensions. The initial source of Zr and Hf was probably zircon (crytolite), which is readily hydrated and breaks down into ZrO2 and SiO2. Together with tungsten leached from the country rock, these components migrated in hydrothermal solutions to cavernous dolomite strata that promoted ore deposition.